ABSTRACT The cake of jatropha seed as by product generated from in situ transesterification process contains high protein (34,68%) and it is not yet optimally benefited. In this research, the cake of jatropha seed was benefited to produce binderless particle board. The purpose of this research is to produce the particle board from the cake of jatropha seed generated by in situ transesterification process with protein as natural binder. The particle board production was carried out under the fol - Sri Lestari dan Ika Amalia Kartika (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT The cake of jatropha seed as by product generated from in situ transesterification process contains high protein (34,68%) and it is not yet optimally benefited. In this research, the cake of jatropha seed was benefited to produce binderless particle board. The purpose of this research is to produce the particle board from the cake of jatropha seed generated by in situ transesterification process with protein as natural binder. The particle board production was carried out under the following process condition : jatropha seed cake moisture content (10- 20%), pressing temperature (140-180oC) and pressing duration (8-12 min). The phisycal and mechanical properties of particle board were tested according to JIS A 5908:2003. Jatropha seed cake moisture content, pressing temperature and pressing duration affected the phisycal and mechanical properties of particle board. The density and moisture content of particle board were respectively 0,79-0,91 g/cm3 and 7,07-10,06%. The swelling in water and water absorpsion after 24 hour water soaking were respectively 14,88-30,60% and 51,67-82,93%, and they were not accordance with JIS A 5908:2003. Modulus of Rupture (MOR) and Modulus of Elasticity (MOE) of particle board were not also accordance with JIS A 5908:2003. Their value respectively were 20,04-65,99 kgf/cm2 and 2340,90-5150,25 kgf/cm2. Generally, the phisycal and mechanical properties of particle board were not accordance with JIS A 5908:2003 except for density and moisture content. Keywords : cake of jatropha seed, particle board, in situ transesterification